Empirical random phase transitions between free flow and synchronized flow at highway bottlenecks. Issue 6 (1st November 2020) - Dülgar, Yildirim; Molzahn, Sven-Eric; Rehborn, Hubert; Koller, Micha; Kerner, Boris S.; Wegerle, Dominik; Schreckenberg, Michael; Menth, Michael; Klenov, Sergey L.
Abstract: Based on a study of probe vehicle data measured on different highways during different days we have revealed some common empirical microscopic characteristic features of sequences of phase transitions from free flow to synchronized flow and back from synchronized flow to free flow occurring before traffic breakdown at a highway bottleneck predicted theoretically by Kerner. Following common empirical features of sequences of these phase transitions have been found: (i) Sequences of empirical phase transitions from free flow to synchronized flow and back from synchronized flow to free flow are observed on different highways at different bottlenecks. (ii) Empirical sequences of the phase transitions exhibit a random character, in particular, at different days very different sequences of phase transitions from free flow to synchronized flow and back from synchronized flow to free flow have been observed at the same bottleneck. (iii) Time durations between the transition from free flow to synchronized flow and the subsequent transition from synchronized flow to free flow within a sequence of the phase transitions are random values. Time intervals between subsequent sequences of the phase transitions are also random values. (iv) Regions of dissolving synchronized flow that result from sequences of phase transitions from free flow to synchronized flow and back from synchronized flow to free flow exhibit random characteristics. (v) Several following each other sequences of phase transitions from free flow to synchronized flow and back from synchronized flow to free flow can lead to waves of synchronized flow between free flow.